2020
DOI: 10.1186/s40249-020-00750-y
|View full text |Cite
|
Sign up to set email alerts
|

Strongyloides stercoralis prevalence and diagnostics in Vientiane, Lao People’s Democratic Republic

Abstract: Background Despite the high prevalence of strongyloidiasis in the Laotian population, Laotian hospitals still lack diagnostic capacity to appropriately diagnose Strongyloides stercoralis infections. This cross-sectional hospital-based study was conducted to assess the prevalence of Strongyloides stercoralis infection among hospitalized patients treated at Mahosot Hospital, the primary reference hospital of Lao People’s Democratic Republic (Lao PDR), and to validate feasible methods for diagnosing S. stercorali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 22 publications
3
22
7
Order By: Relevance
“…A recent study showed that the detection rate of S. stercoralis could be increased when RT-PCR was used instead microscopy based methods [ 34 , 35 ]. In the present study, the detection rate of S. stercoralis by RT-PCR was 28.8%, which is lower than 36.2% previously reported [ 28 ], but it is higher than 13.4% in northwest Ethiopia [ 17 ], 6% in northern Australia [ 36 ], 25% in Lao People’s Democratic Republic [ 12 ]. The variation might be related to accuracy in DNA extraction, preservation and its amplification technique.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…A recent study showed that the detection rate of S. stercoralis could be increased when RT-PCR was used instead microscopy based methods [ 34 , 35 ]. In the present study, the detection rate of S. stercoralis by RT-PCR was 28.8%, which is lower than 36.2% previously reported [ 28 ], but it is higher than 13.4% in northwest Ethiopia [ 17 ], 6% in northern Australia [ 36 ], 25% in Lao People’s Democratic Republic [ 12 ]. The variation might be related to accuracy in DNA extraction, preservation and its amplification technique.…”
Section: Discussioncontrasting
confidence: 79%
“…Among the methods used for the detection of eggs from stool specimens, direct saline microscopy [ 4 ], FECT [ 5 ] and STST [ 6 ] have the lowest sensitivity. The use of these methods for S. stercoralis detection might lead to misdiagnosis and underreporting of strongyloidiasis compared with BCT [ 7 ], APC [ 8 11 ], and RT-PCR or a combination of APC and BCT which have better detection rates [ 12 ]. Because of the low sensitivity of each method for larvae detection, a combination of methods is the most sensitive approach.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microscopy-based direct methods (such as simple wet-smear preparation or Kato-Katz) and even conventional concentration techniques (such as the formalin-ether concentration technique (FECT)) have low sensitivity because of the irregular and often low larval output in latent strongyloidiasis. Concentration techniques specifically designed for the detection of S. stercoralis (such as Baermann or Koga-agar plate-culture (KAPC)) provide more reliable and more sensitive results (each method has a sensitivity in immunocompetent patients of 60%, or 77% when combined) [4]. According to some studies, nucleic acid amplification tests (such as stool PCR) are considered to have better sensitivity than the concentration techniques [5], which are less user-dependent, but expensive and rarely available in low-and middle-income countries.…”
Section: Diagnostic Techniques and Diagnostic Challengesmentioning
confidence: 99%
“…Repeated stool tests (up to three) are generally recommended to increase sensitivity, but this is often not performed because of logistical reasons; Baermann analysis should be performed within a short time after collection, and an interval of at least 72 h needs to be adhered to in between, making this unfeasible in the case of urgent immunosuppressive treatment [6]. If only a single stool sample is available, as is most often the case, our algorithm proposes assessment by stool PCR, KAPC and Baermann concentration in parallel, in order to increase the sensitivity of the diagnostic tests [4].…”
Section: Screening Algorithm For Strongyloidiasismentioning
confidence: 99%